REVISED OCCUPATIONAL CLASSIFICATION INVENTORY (ICO-R): EVIDENCE OF VALIDITY - Santana Batista , Jonatan; Guedes Gondim , Sônia Maria; de Oliveira Magalhães, Mauro; de Souza Brito, Fernanda; Carlotto, Mary Sandra (REOP - Revista Española de Orientación y Psicopedagogía, 2025)
Measures to investigate occupational activities, work design, and person-environment fit are important to help organizations create favorable environments for their workers' performance. The present study has two main objectives. The first was to investigate evidence of validity based on the internal structure of a revised version of the Occupational Classification Inventory (ICO-R), a Brazilian instrument for classifying occupational activities based on the RIASEC model. The second was to examine the relationships of the ICO-R with a measure of Occupational Interests based on the RIASEC model, in order to verify criterion validity and the potential of the ICO-R to assess person-environment fit. A total of 486 workers from different professional fields participated in the study. We used exploratory and confirmatory factor analysis, as well as exploratory graph analysis, to analyze the ICO-R's factor structure. The study presents measures for convergent and criterion validity. The data showed convergent validity and a six-factor solution. The ICO-R proved to be a valid tool to characterize occupations according to the RIASEC model. The revised version of the ICO has excellent psychometric properties and is useful for studies on the occupational environment and person-environment fit.